No contexto da educação infantil : um olhar para as práticas pedagógicas de um CMEI - Sarmento, Jackeline Ferreira (2018)
This study aims to analyze how the Sciences Education is present in the pedagogical practices of Early Childhood Education. The research was developed in the second quarter of 2017, with participants as teachers of a Centro Municipal de Educação Infantil (CMEI) in the eastern part of the city of Manaus. We divided the research into three moments: Historical context of how Child Education was constituted throughout the historical process in the State of Amazonas. In this sense, we present the chosen place for the research that is the result of this process. In the second moment, we present how the practices of Early Childhood Education are organized from the National Curricular Guidelines for Early Childhood Education and we present the work with projects, which are based on the pedagogical practices of the CMEI. In the third moment, we present what we understand by Science Education and how it is present in the pedagogical practices of the CMEI. The theoretical basis was based on authors like Miki (2017), Oliveira (2011) and Arce (2002), Brasil (2009), Larrosa (2011), Hernández (2008), Bachelard (1996) and Marques (2002). The methodological course was based on the qualitative approach and had as instruments of data collection, the questionnaire and the direct observation with record in field diary. Data were analyzed based on the interpretative analysis. The results indicate that the CMEI adopts in its pedagogical practices the work through projects, which seek to articulate the experiences from the proposed theme. It was verified that the teachers understand Science Education in aspects related to nature and the environment. However, we conclude that working with projects opens up many possibilities for developing Science Education in accordance with the idea defended here, which points to the interlocution of knowledge and complementarity between the sciences. Keywords: Early Childhood Education. Pedagogical practices. Science Education